The Juridical Implications for Multiple Positions Performed by Land Deed Officials as State Officials in the Conception of Legal Certainty - Andriyani, Novia (Jurnal Konstatering, 2022)
PPAT is a job that is independent, individual work, without a supervisor, trust work and requires strong morals because there are very few kinds of laws . and regulations, in its implementation it is very vulnerable to various kinds of violations, one of which is concurrent positions. In practice, in practice, over time with the increasing number of people undergoing the PPAT profession from time to time, coupled with technological developments and the opportunity for some PPATs to get as many clients as possible, there are also PPATs who are difficult to get clients. This has made some PPAT individuals to carry out concurrent positions as advocates, become PPATs at the Notary's domicile, and as well as other professions. state officials. 1) knowing and analyzing the legal construction of concurrent positions carried out by the Land Deed Making Official as a state official. 2) Knowing and analyzing the juridical implications of concurrent positions carried out by Land Deed Maker Officials as state officials in the Conception of Legal Certainty. This research method uses normative juridical research, which is a deductive research that begins with an analysis of the articles in the laws and regulations governing the above problems. The specifications used in this study are descriptive analysis. Researchers used normative juridical specifications with primary and secondary data. The primary data used is obtained from binding sources in the form of laws and regulations. The data analysis method used descriptive-qualitative analysis. Based on the research conclusions: 1). Therefore, having multiple positions in the PPAT profession as a state official is allowed and some are not. Concurrent positions permitted by the PPAT position regulations are as follows: 1) PPAT concurrently serves as a notary at the Notary's domicile, Temporary PPAT concurrently serves as sub-district head or village head and Special PPAT concurrently serves as head of the land office. PPAT is prohibited from holding concurrent positions or professions as follows: Advocate, consultant or legal advisor; Civil servants, employees of state-owned enterprises, employees of regional-owned enterprises, private employees; State Officials or Government Employees with Work Agreements (PPPK); Leaders at schools, state universities, or private universities; Licensed surveyors; land appraisers; mediators; and/or other positions prohibited by laws and regulations. 2). The legal consequence of concurrent PPAT positions is a respectful dismissal by the Ministry.Keywords: Concurrent; Deed; Position.